Comparative analysis of sublingual and subcutaneous allergen-specific immunotherapy in children with bronchial asthma sensitized to pollen allergens: effect on cytokine profile and immune response - M.P. Prokhorova; A.V. Kupkina (Zdorovʹe Rebenka)
Background. Allergen-specific immunotherapy is currently the only disease-modifying treatment for allergic diseases. Among its delivery methods, sublingual (SLIT) and subcutaneous (SCIT) immunotherapy are commonly used. However, comparative data on their efficacy and influence on immune response in pediatric patients remain limited. The purpose was to compare the effectiveness of SLIT and SCIT in children with atopic bronchial asthma, focusing on their impact on cytokine profile and immune response. Materials and methods. A total of 70 children aged 5–17 years with mild to moderate bronchial asthma and sensibilization to pollen allergens were enrolled and randomized into two groups: group 1 (n = 35) — SLIT and group 2 (n = 35) — SCIT. A control group of 30 healthy children was included for baseline comparison. The follow-up duration was 1 year. Dynamics of clinical symptoms, eosinophilic inflammation, cellular and humoral immunity indicators, and IL-1β and IL-4 cytokines were assessed. Results. In both groups, a significant improvement in disease control was observed: a decrease in the total score of clinical manifestations of asthma (by 83.4 and 81.3 % in groups 1 and 2, respectively), symptom frequency (by 92.5 and 89.5 %), and the need to use rescue medication (by 95.3 and 93.4 %). A comparable reduction in eosinophilic inflammation was noted: the level of eosinophils in nasal secretion decreased from 34.6 ± 0.6 % to 15.4 ± 0.8 % in group 1 and from 38.9 ± 1.8 % to 16.3 ± 0.5 % in group 2; in peripheral blood — from 14.5 ± 0.5 % to 6.2 ± 1.5 % and from 15.8 ± 0.7 % to 6.3 ± 0.5 %, respectively. Both methods of allergen-specific immunotherapy led to a decrease in IgE, an increase in IgA (p < 0.001), and positive shifts in cellular immunity. The immunoregulatory index increased in the SLIT group from 1.07 ± 0.21 to 1.25 ± 0.17 (p < 0.05), in the SCIT group from 1.15 ± 0.11 to 1.18 ± 0.24 (p > 0.05). A comparable modification of the cytokine profile was found: a decrease in IL-1β (p < 0.05) and IL-4 (p < 0.001) without a statistically significant difference between the groups (p = 0.071 and p = 0.112). Conclusions. SLIT and SCIT have comparable effectiveness in the treatment of children with atopic bronchial asthma, demonstrating comparable effects on immunity and cytokine profile. Both methods provide the formation of immunological tolerance to allergens, suppression of Th2 inflammation and a shift of the immune response towards the Th1 type, which indicates their ability not only to alleviate symptoms, but also to modify the course of the disease.